Magnitude and sources of proactive interference in visual memory. Issue 5 (28th May 2022) - Mercer, Tom; Fisher, Luke P.
ABSTRACT: Proactive interference – the disruptive effect of old memories on new learning – is a long-established forgetting mechanism, yet there are doubts about its impact on visual working memory and uncertainty about the kinds of information that cause proactive interference. The present study aimed to assess these issues in three experiments using a modified recent probes task. Participants encoded four target images on each trial and determined whether a probe matched one of those targets. In Experiment 1, probes matching targets from trial N -1 or N -3 damaged responding in relation to a novel probe. Proactive interference was also produced by probes differing in state to a previously experienced target. This was further assessed in Experiments 2 and 3. Here, probes differing in colour to a previous target, or matching the general target category only, produced little proactive interference. Conversely, probes directly matching a prior target, or differing in state information, hindered task performance. This study found robust proactive interference in visual working memory that could endure over multiple trials, but it was also produced by stimuli closely resembling an old target. This challenges the notion that proactive interference is produced by an exact representation of a previously encoded image.